Strategic Collaboration and Sustainable Competitive Advantage Capabilities: A Confirmatory Factor Analysis (CFA) Approach - Trisandi Rizki, Lutfi; Priyadi, Iwan (LifeSciFi, 2025)
This study aims to examine and validate the constructs of strategic collaboration capabilities, entrepreneurial leadership capabilities, digital transformation capabilities, strategic agility, and sustainable competitive advantage using Confirmatory Factor Analysis (CFA) within the Structural Equation Modeling (SEM) framework. Strategic collaboration is essential for organizations to foster innovation and adaptability through partnerships, while sustainable competitive advantage reflects a firm's ability to maintain superior performance over time. The research tested five observed indicators for each construct—strategic collaboration capabilities, entrepreneurial leadership capabilities, digital transformation capabilities, strategic agility, and sustainable competitive advantage—to assess factor structure and convergent validity. Results show that all factor loadings exceed the 0.60 threshold, confirming strong convergent validity for each construct. While the model fit indices for strategic collaboration indicate room for improvement, particularly in RMSEA and CMIN/DF, indices such as CFI and TLI fall within acceptable ranges. In contrast, the sustainable competitive advantage construct shows a favorable model fit, with factor loadings ranging from 0.740 to 0.975 and strong fit indices. These findings validate the reliability and construct validity of the examined constructs within the SEM framework.